1996
DOI: 10.1021/jp952321g
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Large Changes in Temperature and Pressure on the Thermodynamic Properties of Micellization and on the Distribution Constant of a Polar Solute in Micellar Solutions

Abstract: Density measurements of pentanol (PentOH)-dodecyltrimethylammonium bromide (DTAB)-water mixtures as functions of both alcohol and surfactant (m S ) concentrations were carried out at 0.1 MPa from 45 to 75°C and at 19 MPa from 25 to 130°C. The standard (infinite dilution) partial molar volumes and expansibilities of DTAB in water and the corresponding properties in the micellar phase were calculated from the experimental data. As far as PentOH in DTAB micellar solutions is concerned, with the exception of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 52 publications
2
15
0
Order By: Relevance
“…In the premicellar region, H h 2 was expressed in terms of the temperature derivative of the surfactant's mean activity coefficient γ ( , described by the Guggenheim's approximation. 4,5,19,20 For all the measured surfactants the critical micelle concentrations determined by employing Philips criter-ion 21,22 on the experimental titration curves agree well with the corresponding values obtained by other methods. 11,12,23 Fitting of the simulated calorimetric titration curves to those determined experimentally showed that the applied fitting procedure can provide only ∆H M values while it is not able to give any information on the micelle ionization parameter p/n.…”
Section: Introductionsupporting
confidence: 76%
“…In the premicellar region, H h 2 was expressed in terms of the temperature derivative of the surfactant's mean activity coefficient γ ( , described by the Guggenheim's approximation. 4,5,19,20 For all the measured surfactants the critical micelle concentrations determined by employing Philips criter-ion 21,22 on the experimental titration curves agree well with the corresponding values obtained by other methods. 11,12,23 Fitting of the simulated calorimetric titration curves to those determined experimentally showed that the applied fitting procedure can provide only ∆H M values while it is not able to give any information on the micelle ionization parameter p/n.…”
Section: Introductionsupporting
confidence: 76%
“…As far as NaDS is concerned, at 25 °C and 19 MPa as well as at 65 °C and both pressures, ( V Φ ,S − ) increases monotonically with m S in the whole range of m S studied, and therefore, the cmc is not evident (Figures and ). NaDS behaves similarly to dodecyltrimethylammonium bromide (DTAB); however, for the latter the cmc values were always detected.…”
Section: Resultsmentioning
confidence: 99%
“…In the following, we shall focus our attention on and on the pressure effect on it since studying the temperature coefficient of is equivalent to studying the pressure coefficient of As observed for DeTAB 11 and DTAB, of each surfactant is positive and slightly decreases with pressure. Due to the lack of values for NaDS, we can compare only NaDeS to DeTAB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentration of DTAB, c DTAB , in solutions varied from 0.3 to 10 mM, whereas the time of adsorption changed from 30 to ca. 20 h. To avoid adsorption of micelles on mica, c DTAB was maintained below its critical concentration of micellization (cmc), that is, below 0.0154 M at 20 °C …”
Section: Resultsmentioning
confidence: 99%